Environmental Scanning and Prioritization of Issues in Marine Tourism Development in Ternate City, Indonesia - Alma'arif Alma'arif; Abdul Fatah Satyapraja; Sarmila Md Sum (Universitas Muhammadiyah Yogyakarta, 2025)
The management of Hol Sulamadaha Bay in Ternate City remains suboptimal, as reflected in the declining number of tourists visits due to the lack of prioritization in development efforts. This study aims to analyze the strategic environment and identify key strategic priorities for the development of marine tourism in Ternate. Grounded in Wheelen and Hunger's strategic management theory—specifically strategic environmental analysis and employing the Analytical Hierarchy Process (AHP), the research adopts a post-positivist paradigm. Data collection combined qualitative methods, including interviews and documentation, with quantitative analysis through expert-validated questionnaires. Key informants included government officials, private sector representatives, local communities, tourists, and residents from remote areas. The findings reveal four pressing strategic issues: (1) limited involvement of the Tourism Awareness Group (TAG), (2) low levels of tourism literacy, (3) inadequate access, facilities, and infrastructure, and (4) limited community participation in tourism development. Moreover, the study emphasizes the role of mutual trust between government and local communities as a critical factor for encouraging inclusive participation, from policy planning through to implementation and evaluation. The novelty of this study lies in its integration of strategic environmental analysis and AHP to assess marine tourism development while foregrounding the socio-cultural dynamics particularly trust, belief systems, and local values that influence community engagement. This holistic approach offers a new perspective for developing inclusive, culturally grounded strategies to revitalize marine tourism in small island regions like Ternate.